Exploring students’ barriers in reading digital books: A case study of English education students at IAIN Palopo - Furwana, Dewi; Teresa Linse, Caroline; Andriani, Nur; Mifta, Nurul (Universitas Muhammadiyah Sidoarjo, 2025)
Technological advancements have transformed education, including the use of digital books as learning media. Despite their potential, many students still encounter obstacles in accessing and utilizing digital books effectively. This study investigates the barriers faced by students of the English Language Education Study Program at IAIN Palopo in reading digital books. Using a qualitative case study approach, data were collected through unstructured interviews with 12 students from the Faculty of Education and Teacher Training. The data were analyzed through three stages: data reduction, data display, and conclusion drawing. The results reveal seven primary barriers: (1) limited device storage and low battery life hinder access to digital books (Device Access); (2) unstable internet connections in students' local areas affect accessibility (Internet Connectivity); (3) prolonged screen time leads to eye strain (Eyestrain); (4) students experience dizziness and fatigue after extended reading sessions (Reading Fatigue); (5) distractions from social media notifications reduce focus (Concentration and Retention); (6) unattractive digital book formats discourage engagement (Format Issues); and (7) some students cannot access certain materials due to financial constraints (Socioeconomic Barriers). These findings highlight the need for more accessible and student-friendly digital reading solutions. HIGHLIGHTS: Technological and infrastructural limitations such as insufficient device storage, batteryissues, and unstable internet are major obstacles impeding students’ access to digital books. Physiological and cognitive barriers, including digital eye strain, reading fatigue, anddistractions from mobile notifications, significantly reduce reading comprehension andretention. Socioeconomic factors and format-related discomfort, such as unaffordable e-books andpoor digital design, further hinder equitable and effective engagement with digital learningresources.